The behavioral specificity of child-to-parent violence - Cortina, Helena; Martín, Ana M. (Anales de Psicología / Annals of Psychology, 2020)
Child-to-parent violence (CPV) is a type of domestic violence that has gained social and scientific visibility in recent years. The objective of this study is to analyze different forms of CPV and their relationship with two groups of variables. The first group includes gender, age, family structure, school year, academic performance, drug use, frequency of drug use and diagnosis of psychopathology. The second analyzes exposure to violence, parental warmth, self-concept, sexism, narcissism and psychopathy. The participants were 225 high school students from 14 to 20 years old, 54.7% of them girls. The CPV rates were lower than those of previous Spanish studies but similar to those in other countries. Most participants engaged in only one behavior, insulting, and hitting never appeared alone, but in combination with at least two other behaviors. The analysis of the data showed that the ability of the variables under study to predict CPV varies for each specific behavior. The results are discussed by proposing that future studies consider CPV as a social problem that goes beyond parent-child relations.